2020
DOI: 10.3389/fphar.2020.564281
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Hydrogen Sulfide Donors in Common Kidney Diseases

Abstract: Hydrogen sulfide (H 2 S) plays a key role in the regulation of physiological processes in mammals. The decline in H 2 S level has been reported in numerous renal disorders. In animal models of renal disorders, treatment with H 2 S donors could restore H 2 S levels and improve renal functions. H 2 S donors suppress renal dysfunction by regulating autophagy, apoptosis, oxidative stress, and inflammation through multiple signaling pathways, such as TRL4/NLRP3, AMP-activated protein kinase/mammalian target of rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 201 publications
(336 reference statements)
0
17
0
3
Order By: Relevance
“…Previous research also found that endogenous H 2 S supplement ameliorated carbon tetrachloride and high fat diet induced liver fibrosis in rats [11]. H 2 S significantly alleviated renal fibrosis by attenuating collagen accumulation and extracellular matrix remodeling in the kidney of diabetic mice and gentamicin-induced rats [12]. H 2 S also prevented smoke-induced pulmonary fibrosis in rats and alleviated systemic sclerosis associated lung fibrosis in mice [13].…”
Section: Introductionmentioning
confidence: 80%
“…Previous research also found that endogenous H 2 S supplement ameliorated carbon tetrachloride and high fat diet induced liver fibrosis in rats [11]. H 2 S significantly alleviated renal fibrosis by attenuating collagen accumulation and extracellular matrix remodeling in the kidney of diabetic mice and gentamicin-induced rats [12]. H 2 S also prevented smoke-induced pulmonary fibrosis in rats and alleviated systemic sclerosis associated lung fibrosis in mice [13].…”
Section: Introductionmentioning
confidence: 80%
“…In addition, CSE is commonly expressed in endothelial and mesangial cells and podocytes [51]. In kidney diseases, H 2 S ameliorates renal damage [52]. It has been shown that H 2 S attenuates kidney injury during I/R and diabetic kidney disease (DKD).…”
Section: Figurementioning
confidence: 99%
“…Depending on its origin, AKI affects preferentially either glomerular or tubular structures of the kidney. A protective role of hydrogen sulfide in AKI on all kidney segments, including the tubules, is reviewed elsewhere [ 7 , 60 , 61 ]. The effects of AKI in the context of different forms of glomerulonephritis is, so far, poorly understood.…”
Section: The Role Of H 2 S In Glomerular Pathophys...mentioning
confidence: 99%
“…This stress situation interferes with the complex and fine-tuned intraglomerular crosstalk between mesangial cells, glomerular epithelial cells (podocytes) and glomerular endothelial cells resulting in a disturbance of glomerular integrity and function [ 3 , 4 , 5 , 6 ]. In the last decade, the research on H 2 S in animal models revealed promising results for the pharmacological use of H 2 S-releasing drugs for the treatment of glomerular kidney diseases [ 7 ]. Here, we briefly discuss the role of H 2 S in glomerulopathies with a focus on the molecular mechanisms of production and action of this signalling mediator.…”
Section: Introductionmentioning
confidence: 99%